Avaliação de métodos de análises para determinação da contagem de células somáticas no leite cru, mantido em tanque de resfriamento - Pereira Neto, Manoel (2012)
We analyzed the quality of raw milk from eight dairy farms in Rio Grande do Norte stored in a cooling tank , in order to evaluate methods for determining somatic cell counts (SCC). The Somaticell® kit and a portable Direct Cell Counter (DCC) were compared with each other and with the MilkoScanTM FT+ (FOSS Denmark), which uses Fourier Transform Infrared (FTIR) spectroscopy). Direct cell counter data were processed for somatic cell scores (log-transformed somatic cell count) and analyzed with the SAS®, statistical package , Statistical Analysis System, (SAS, INSTITUTE, 1998). Comparison of means and correlation of somatic cell scores were conducted using Pearson s correlation coefficient and the Tukey Test at 1 %. No significant difference was observed for comparison of means. The correlation between somatic cell scores was significant, that is, 0.907 and 0.876 between the MilkoScanTM FT+ and the Somaticell® kit and Direct Cell Count (DCC) respectively, and 0.943 between the Somaticell® kit and Direct Cell Count (DCC). The methods can be recommended for monitoring the quality of raw milk kept in a cooling tank in the production unit